Effective Utilization of Rolled Sections in Hydrocarbon Plant Structures - Papia Mandal; Karnam Madhavilatha; Anurag Sinha (PREPARE@u® | IEI Conferences, 2021)
“Make in Steel” strategy is one of the core contributor to take India towards $5-trillion economy goal. Hydrocarbon industry is one of the major sectors, where structural steel consumption is substantial. Along with the growth of the nation, capacities of refineries and petrochemicals are also growing noticeably and thereby demanding variety of structural steel rolled sections in huge quantity. Age-old vicious cycle of demand-supply is continuing to be unbeatable for rolled sections as well. In past few years, manufacturers have geared up to produce more variety of sections. Though it is fascinating for the structural engineers to have more options, tradeoff between various sections becomes difficult; moreover ordering process and inventory management get more stringent for both of the contractors and manufacturers. Various structural components have a particular pattern of axial force and bending moment carrying mechanism; by deep understanding of the same and mapping certain types of rolled sections along with a specific types of structural components, sections can be effectively utilized and variety of sections can be reduced thereof. This paper aims at reducing variety of structural steel rolled sections, by effective utilization of axial and bending capacities of the sections, particularly for structures associated with hydrocarbon industry.